Botulinum A Toxin Intravesical Injections in the Treatment of Refractory Overactive Bladder in Patients with Parkinson's Disease - Giannantoni, Antonella; Proietti, Silvia; Conte, Antonella; Porena, Massimo; Berardelli, Alfredo (IntechOpen, 2011)
None